Developmental programming of the cell stress response and metabolic inflammation in liver and adipose tissue in an ovine model - Saroha, Vivek (2017)
A state of chronic metabolic inflammation and activation of the cell stress response in organs such as liver and adipose tissue are important pathogenic adaptations with the onset of obesity and the metabolic syndrome. The extent to which these processes are modulated by the early life nutritional experience is not well established, especially in large animal models. The overall aim of this thesis was to identify whether nutritional programming during prenatal and postnatal development enhances metabolic inflammation and cell stress response of obesity. A nutritional model of fetal growth restriction achieved by maternal nutrient restriction (NR) to 60% of requirements during late gestation (110 days to term at 147 days) in twin bearing sheep was used. Combination of prenatal and postnatal nutritional interventions were studied with the following three study protocols: